Education and Reeshaping of Female Identity in nervous Conditions by Tsitsi Dangraembga - Ammari, Chemsa, Khouloud Lina (University of El-oued, 2021)
The study under investigation examines the issue of education in Nervous conditions (1988) by the Zimbabwean novelist Tsitsi Dangarembga. It also tries to highlight the influences of colonial education on the female identity among the colonized Zimbabwean community. This research aims at providing a clear analysis on the way the colonial education affects the formation of the female identity through the analysis of the theme of education in the novel, in addition to the study of the female character ''MaSingayi '', ''Maiguru'', ''Loucia'' and paying a special attention to the two protagonist ''Tambu'' and ''Nyasha''. The study conducts a descriptive analytical method depending on the post colonial feminist theory to demonstrate the statue of female identity and the effects of the colonial education on them. The findings of the study reveals that education does not necessary prevent women from being entrapped. In addition, it may affect negatively the formation of female identity which leads to lose the national identity as expressed by the character of '' Nyasha'' who suffers from identity crisis. Furthermore, ''Tambu'' realizes that the formation of her female identity depends on her choices by refusing the total acceptances of the colonizer ideology that is delivered through its educational system besides questioning things in building her female identity above the root of her national identity. Finally, the implications for further research for this novel is recommended so as to shed light on other aspects.
Keywords: postcolonial feminism, colonial education, female identity